POTENSI TANAH MENGEMBANG BERDASARKAN KADAR LEMPUNG DI KABUPATEN BEKASI, JAWA BARAT - Dewi Ulfa Astriani; Dicky Muslim; Agung Mulyo; Tulus Pramudyo (PPSDM Geominerba, 2022)
Bekasi Regency is composed of soft soil material that has swelling potential due to its expansive properties. This study aims to identify the swelling potential of soil using clay content parameters in six undisturbed samples. The samples were tested on basic physical properties to identify soil characteristics. The results showed that the study area is composed of high-plasticity silt soils (MH) based on the USCS. The percentage of clay is 5.5% to 20.1% and the percentage of silt is 33.2% to 85.7% indicating a more dominant silt content. Clay activity ranges from 2,418 to 4,973%, indicating the presence of montmorillonitic minerals. The swelling potential shows a value from 3.5817 to 33.525% including medium to very high potential. The difference in swelling potential in the soil samples can be caused by several factors such as the percentage of clay, moisture content, and plasticity index.